Drastic solid-state luminescence color tuning of an archetypal Ir(iii) complex using polyoxometalates and its application as a vapoluminescence chemosensor. Issue 48 (29th November 2016) - Bolle, P.; Serier-Brault, H.; Génois, R.; Faulques, E.; Boulmier, A.; Oms, O.; Lepeltier, M.; Marrot, J.; Dolbecq, A.; Mialane, P.; Dessapt, R.
Abstract : New assemblies based on the archetypal [Ir III (ppy)2 (bpy)] + complex and a series of polyoxometalates exhibit highly tunable phosphorescence and vapoluminescence properties for detection of volatile organic compounds. Abstract : Using a straightforward one-step synthetic procedure, the solid-state phosphorescence of the archetypal [Ir III (ppy)2 (bpy)] + complex has been successfully tuned from green to yellow, orange and red by its association with a series of polyoxometalates. Such new materials can exhibit remarkable vapoluminescence properties for the detection of volatile organic compounds (VOCs) even in the presence of moisture via a new polymorphous conversion mechanism.